2019
DOI: 10.1128/aem.02943-18
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Morphotype Analysis of “ Candidatus Accumulibacter” Using Fluorescence In Situ Hybridization-Staining-Flow Cytometry

Abstract: “Candidatus Accumulibacter” is the dominant polyphosphate-accumulating organism (PAO) in denitrifying phosphorus removal (DPR) systems. In order to investigate the community structure and clade morphotypes of “Candidatus Accumulibacter” in DPR systems through flow cytometry (FCM), denitrifying phosphorus removal of almost 100% using nitrite and nitrate as the electron acceptor was achieved in sequencing batch reactors (SBRs). An optimal method of flow cytometry combined with fluorescence in situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 56 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Wang et al and Xin et al used metagenomic studies to show that Rhodophyta plays a leading role in denitrification in wastewater treatment systems [40,41]; different genera of Rhodocyclaceae have special treatment functions. For example, the studies of McIlroy et al and Li et al showed that Rhodocyclaceae appears alternately in the enhanced biological phosphorus removal (EBPR) bioreactor under anaerobic and aerobic conditions to enhance the phosphorus removal effect [42,43].…”
Section: Bacterial Community Structure Among the Biological Treatment Systemsmentioning
confidence: 99%
“…Wang et al and Xin et al used metagenomic studies to show that Rhodophyta plays a leading role in denitrification in wastewater treatment systems [40,41]; different genera of Rhodocyclaceae have special treatment functions. For example, the studies of McIlroy et al and Li et al showed that Rhodocyclaceae appears alternately in the enhanced biological phosphorus removal (EBPR) bioreactor under anaerobic and aerobic conditions to enhance the phosphorus removal effect [42,43].…”
Section: Bacterial Community Structure Among the Biological Treatment Systemsmentioning
confidence: 99%